At the intersection of content and materiality: A texto-material perspective on agency in the use of media technologies - Siles González, Ignacio (2012)
This article examines the scholarship on agency in the appropriation of information and communication technologies in communication and media research and science and technology studies. Work in these fields has been limited by inability to depict the ways in which materiality and content intersect in technology use and why that matters for making sense of agency dynamics. This article articulates a ‘‘texto-material’’ perspective that combines analysis of users’ content creation and interpretation practices with an assessment of how they appropriate and shape artifacts. Building on the small body of work that has explored the intersections of these dimensions, we propose a programmatic research agenda that begins operationalizing this perspective by fostering an examination of media technologies as texto-material assemblages.